Six Weeks of Boxing Training Lowers Blood Pressure and Improves Vascular Function in Young Men and Women with Elevated Blood Pressure or Stage 1 Hypertension - Morales-Acuna, F (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
(1) Background: Early stages of hypertension, including elevated blood pressure and stage 1 hypertension, are known to increase cardiovascular risk and mortality. Exercise is widely recommended for blood pressure management; however, the optimal exercise modality and the underlying vascular mechanisms remain uncertain. (2) Methods: This study investigated the effects of boxing training on clinical and vascular parameters in young adults with elevated blood pressure or stage 1 hypertension. Twenty-four participants (mean age 25.4 +/- 4.9 years) were randomly assigned to a boxing training group or a control group. Over six weeks, the intervention group performed boxing training three times per week, consisting of ten three-minute rounds interspersed with one-minute rests, while controls completed flexibility and balance exercises. (3) Results: Boxing training produced significant group-by-time interactions for peripheral and central blood pressure, endothelial function, and carotid artery structure. Reductions were observed in systolic (similar to 16 mmHg) and diastolic (similar to 10 mmHg) blood pressure and in central systolic pressure (similar to mmHg). Vascular function improved, as indicated by greater brachial and popliteal flow-mediated dilation and increased forearm and calf blood flow, accompanied by enhanced nitric oxide bioavailability and reduced inflammation. (4) Conclusions: These findings suggest that boxing training is an effective and time-efficient exercise modality for improving vascular health and managing early hypertension in young adults.
Keywords: boxing training; high blood pressure; endothelial function